Cardiac arrest: resuscitation and reperfusion - Patil, Kaustubha D; Halperin, Henry R; Becker, Lance B (Circulation research, 2015)
The modern treatment of cardiac arrest is an increasingly complex medical procedure with a rapidly changing array of therapeutic approaches designed to restore life to victims of sudden death. The 2 primary goals of providing artificial circulation and defibrillation to halt ventricular fibrillation remain of paramount importance for saving lives. They have undergone significant improvements in technology and dissemination into the community subsequent to their establishment 60 years ago. The evolution of artificial circulation includes efforts to optimize manual cardiopulmonary resuscitation, external mechanical cardiopulmonary resuscitation devices designed to augment circulation, and may soon advance further into the rapid deployment of specially designed internal emergency cardiopulmonary bypass devices. The development of defibrillation technologies has progressed from bulky internal defibrillators paddles applied directly to the heart, to manually controlled external defibrillators, to automatic external defibrillators that can now be obtained over-the-counter for widespread use in the community or home. But the modern treatment of cardiac arrest now involves more than merely providing circulation and defibrillation. As suggested by a 3-phase model of treatment, newer approaches targeting patients who have had a more prolonged cardiac arrest include treatment of the metabolic phase of cardiac arrest with therapeutic hypothermia, agents to treat or prevent reperfusion injury, new strategies specifically focused on pulseless electric activity, which is the presenting rhythm in at least one third of cardiac arrests, and aggressive post resuscitation care. There are discoveries at the cellular and molecular level about ischemia and reperfusion pathobiology that may be translated into future new therapies. On the near horizon is the combination of advanced cardiopulmonary bypass plus a cocktail of multiple agents targeted at restoration of normal metabolism and prevention of reperfusion injury, as this holds the promise of restoring life to many patients for whom our current therapies fail.